Reframing intercultural communication in BIPA teaching materials: A cultural perspective from West Sumatra - Tiawati, Refa Lina; Rahmat, Wahyudi; Ottman , Olsen (BAHASTRA, 2026)
This study examines the representation of Minangkabau local wisdom in five nationally standardized BIPA (Indonesian for Foreign Speakers) textbooks and three supplementary materials utilized in Padang. Employing qualitative content analysis alongside critical discourse analysis (CDA), the research investigates how sociocultural knowledge is constructed, prioritized, or silenced in pedagogical materials. The findings reveal three critical gaps: (1) the complete absence of Kato Nan Ampek (the traditional speech-level system); (2) only two out of twelve Sumbang Duo Baleh behavioral norms are implicitly referenced; and (3) the matrilineal kinship system is consistently framed as a static ‘traditional custom’ rather than a dynamic, living social structure. These omissions point to a systematic marginalization of Minangkabau sociopragmatic knowledge, which may hinder learners’ development of authentic intercultural competence. To address these empirical and pedagogical gaps, the study proposes the BITD (Budaya, Identitas, Teks, dan Dialog) region-based thematic model, which integrates localized wisdom into BIPA instruction through contextually grounded materials, pragmatic awareness, and participatory learning frameworks. This research contributes to ongoing debates on decolonizing language pedagogy and offers actionable guidelines for curriculum developers, textbook authors, and BIPA instructors seeking to foster culturally responsive language education.